Absorption turbulence-radiation interactions in sooting turbulent jet flames. (November 2017) - Consalvi, J.L.; Nmira, F.
Highlights: Absorption TRI in sooting diffusion flames of different optical thicknesses. Instantaneous scalars are generated by stochastic time and space series. The contribution of gas phase to absorption TRI can be neglected. Soot absorption TRI tends to reduce absorption. OTFA is a rather good approximation for sooting jet diffusion flames. Abstract: The effects of absorption Turbulence-Radiation Interactions (TRI) on radiative heat transfer are investigated along characteristic diametric paths of three ethylene/air flames using a stochastic space and time series model. The three flames cover a wide range of scales and optical thicknesses. Model results show that the contribution of absorption TRI to the total absorption increases with the optical thickness but remains lower than 10%. Absorption TRI is largely dominated by soot radiation. The cross-correlation between the soot absorption coefficient and the radiative intensity is found to be mainly negative, leading to an overall negative absorption TRI. Finally, the Optically Thin Fluctuation Approximation can be applied to the modeling of turbulent jet flames despite noticeable discrepancies on mean spectrally-integrated radiative intensity for the large-scale optically-thick flame.